Mapping the chemistry and taxonomy of antimalarial sponge-associated microorganisms - Casanova, Jannelle R. (Animo Repository, 2016)
In this study, we investigated the potential of sponge-associated microorganisms as sources of antimalarial compounds. Sponge-associated microorganisms were grown in R2A or ISP2 media. Culture broths were fractionated using Diaion HP-20 resin and MeOH:H2O gradient elution to yield four fractions per isolate. The antimalarial properties of the resulting fractions were assessed at a concentration of 5 μg/mL using ring-stage Plasmodium falciparum W2 strain parasites with chloroquine (50 μg/mL) as positive control. Parasite growth inhibition was determined by quantifying the fluorescence of the DNA-binding dye YOYO-1 using flow cytometry measurements. Phylogenetic analysis of the 16S rRNA gene sequence, HPLC-based chemical profile and antimalarial activity were integrated to identify promiscuous hitters and potentially unique bioactives. Screening of 636 fractions generated from 159 sponge-associated microorganisms resulted in 34 fractions exhibiting significant antimalarial property (≤20% maximum proliferation of P. falciparum). 16S rRNA gene sequencing was used for taxonomic identification of the source marine microorganisms of the bioactive fractions was based on 16S rRNA gene sequencing. Chemical profiling of the bioactive fractions was carried out using reversed phase HPLC. The chemical profiles among members of the same clade showed significant similarities, indicating a common antimalarial compound across different extracts within the same clade. Different bioactive clades showed distinct chemistries (aside from Gordonia and Streptomyces sp.), indicating unique bioactive principles among the antimalarial extracts.